Cyclic Voltammetric Investigation of Dopamine at Poly-(Gabapentin) Modified Carbon Paste Electrode - M. T. Shreenivas; B. E. Kumara Swamy; Umesh Chandra; B. S. Sherigara (International Journal of Electrochemistry)
The poly (gabapentin) film was prepared on the surface of carbon paste electrode by electrochemical method using cyclic voltammetric technique. The poly (gabapentin) film-modified carbon paste electrode was calibrated with standard potassium ferrocyanide solution in 1 M KCl as a supporting electrolyte. The prepared poly (gabapentin) film-coated electrode exhibits excellent electrocatalytic activity towards the detection of dopamine at physiological pH. The scan rate effect was found to be diffusion-controlled electrode process. The concentration effect of dopamine was studied, and the redox peak potentials of dopamine were dependant on pH.